Prognostic implications of mismatch repair deficiency in patients with nonmetastatic colorectal and endometrial cancer. Issue 2 (12th March 2019) - Fountzilas, Elena; Kotoula, Vassiliki; Pentheroudakis, George; Manousou, Kyriaki; Polychronidou, Genovefa; Vrettou, Eleni; Poulios, Christos; Papadopoulou, Eirini; Raptou, Georgia; Pectasides, Eirini; Karayannopoulou, Georgia; Chrisafi, Sofia; et al.
Abstract : Background: The clinical relevance of mismatch repair (MMR) status in patients with nonmetastatic cancer across tumour types remains unclear. Our goal was to investigate the prognostic role of MMR deficiency in patients with stage I-III colorectal and endometrial cancer. Methods: Patients with nonmetastatic colorectal and endometrial cancer with tumour tissue available for analysis were identified through the Hellenic Cooperative Oncology Group (HeCOG)'s tumour repository. Patients had been referred to Departments of Medical Oncology affiliated with HeCOG. MMR protein expression was evaluated by immunohistochemistry. The primary outcome measure was overall survival (OS). Results: From May 1990 to September 2012, 1158 patients with nonmetastatic colorectal (N = 991) and endometrial cancer (N = 167) were identified (median age: 64 years, men: 544). All patients with colorectal and 109 (65%) with endometrial cancer had received adjuvant treatment. MMR deficiency was observed in 114 (11.5%) of colorectal and 80 (47.9%) of endometrial tumours. More commonly deficient proteins were PMS2 (69 patients, 7%) and MLH1 (63 patients, 6.5%) in colorectal cancer and MSH2 (58 patients, 34.7%) in endometrial cancer. Colorectal MMR-deficient (dMMR) tumours were more likely to be right sided (65 % dMMR vs 27 % proficient MMR, pMMR; p < 0.001), high grade (31% vs 15%, χ 2, p < 0.001) and with a mucinous component (64% vs 42%, p < 0.001). Endometrial dMMR tumours were more often of endometrioid histology (51.4 % endometrioid vs 20 % serous/clear cell, p = 0.020). Compared with MMR proficiency, MMR deficiency was associated with improved OS in patients with endometrial cancer (HR = 0.38, 95% CI 0.20 to 0.76, p = 0.006), but not in patients with colorectal cancer (HR = 0.73, 95% CI 0.49 to 1.09, p = 0.130). After adjusting for age, stage and grade, MMR deficiency maintained its favourable prognostic significance in patients with endometrial cancer (HR = 0.42, 95% CI 0.20 to 0.88, p = 0.021). Conclusions: DMMR was associated with improved outcomes in patients with nonmetastatic endometrial cancer, but not in patients with nonmetastatic colorectal cancer who received adjuvant chemotherapy.